If it's not what You are looking for type in the equation solver your own equation and let us solve it.
76+36=14x-2
We move all terms to the left:
76+36-(14x-2)=0
We add all the numbers together, and all the variables
-(14x-2)+112=0
We get rid of parentheses
-14x+2+112=0
We add all the numbers together, and all the variables
-14x+114=0
We move all terms containing x to the left, all other terms to the right
-14x=-114
x=-114/-14
x=8+1/7
| (5x+15°)=(4x-6°) | | x-39=3/4-x | | 17-14k=-7-6k | | 3x+3=2/3 | | |3x-4|=10 | | 4y-10=2y-12 | | 8×(3-x)=x+25 | | 7b-b-2b-b=12 | | 10g+4g-13g+2g+2g=15 | | (43x+36)+(54x+14)=180 | | 10x-9=4x+37 | | 10g+4g-13g+2g=15 | | T=p+18 | | 35+0.20x=98 | | 4b+3b-b=6 | | 5x-37=300 | | 13s-10s=18 | | 6=7y-3 | | 6(d+2)=18 | | 5w-4w=18 | | -22x-132=-44 | | 19d+d=20 | | -7b+6=-2b+1 | | 17=c+2 | | 20m-19=16 | | 14x-22=-86 | | 14−5x=4 | | -2(x+3)=-4+5(x-2) | | 0.7y+2=0.5y+6 | | 17=8r | | 4(m+2)+1=5(m+1)+m | | 6k-7k-10=3k+2 |